Spotlight on Data : Caching Big Data for Machine Learning at Uber with Zhenxiao Luo - Luo, Zhenxiao (O'Reilly Media, Inc., 2019)
From determining the most convenient rider pickup points to predicting the fastest routes, Uber uses data-driven machine learning to create seamless trip experiences. Within engineering, big data and machine learning inform decision-making processes across the board. As Uber expands to new markets, the ability to accurately and quickly use data to make predictions becomes even more important. In this case study, Uber's Zhenxiao Luo details the company's machine learning architecture and talk about how Uber uses big data to power machine learning jobs. Recorded on June 17, 2019. See the original event page for resources for further learning. Find future live events to attend or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Data, you'll learn about, discuss, and debate the tools, techniques, questions, and quandaries in the world of data. You'll discover how successful companies leverage data effectively and how you can follow their lead to transform your organization and prepare for the Next Economy.